IMPLEMENTASI MODEL PEMBELAJARAN PROBING PROMPTING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V MIN SIBUHUAN - Nur Saniah Nasution; Lailan Aprina Siregar; Rizki Hamdan Saputra (CV. ADIBA ASIHA AMIRA, 2023)
The aim of this research is to determine (1) the learning motivation of fifth grade students at MIN Sibuhuan. (2) Implementation of the probing prompting learning model to increase the learning motivation of class V MIN Sibuhuan students. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out in class V of MIN Sibuhuan. The data sources in this research were divided into two, namely (1) primary data, namely students of class V MIN Sibuhuan (2) secondary data, namely class V teachers of MIN Sibuhuan. Data collection techniques in this research were obtained through observation and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the research results, it can be concluded that (1) The learning motivation of class V MIN Sibuhuan students pre-cycle is still low, namely 4 students or 12.50% have